ANALYSIS OF THE OPTIMIZATION OF CAPITAL STRUCTURE AND CAPITAL BUDGETING AT PT PP SEMARANG DEMAK - Rohmat, Fatur; Nahda, Katiya (Publikasi Inspirasi Indonesia, 2025)
PT PP Semarang Demak is a company engaged in the construction and management of toll roads on the Semarang-Demak section with a length of 26.40 KM. The investment made according to the capital expenditure value is 5,9 trillion with a capital structure composition of 70% debt and 30% equity. This study aims to identify the optimization of determining the composition of the capital structure towards creating corporate value. The method used is a qualitative approach, conducting direct observation during the internship and interviews with 5 selected respondents. The result showed that the determination of capital structure uses several methods to determine investment feasibility, namely Net Present Value (NPV), Internal Rate of Return (IRR), Weighted Average Cost of Capital (WACC), and Payback Period. At the beginning of determining the composition of the capital structure, it was found that the NPV value was 2.196.701 (in million), IRR 11,6%, WACC 10,54%, and Payback Period 10 – 15 years. It proves the investment project is feasible to continue because the NPV is positive and provides profit, IRR more than WACC. However, there are obstacle in the Semarang-Demak section 1 toll road construction project that pose a challenge for PT PP Semarang Demak in not maximizing revenue which has an impact on the ability to fulfill its debt. This can be followed up by the company to reconsider the portion of debt and equity with several strategies, one of which is to reduce the debt and improve the equity portion.